Unsettling Sikh and Muslim conflict mistaken identities, forced conversions, and postcolonial formations - Sian, Katy P. (Lexington Books, 2013)
This book interrogates such explanations, by focusing upon the relationship between diaspora and the articulation of a postcolonial Sikh identity.